2010
DOI: 10.5194/acp-10-1417-2010
|View full text |Cite
|
Sign up to set email alerts
|

A laboratory based experimental study of mercury emission from contaminated soils in the River Idrijca catchment

Abstract: Abstract.Results obtained by a laboratory flux measurement system (LFMS) focused on investigating the kinetics of the mercury emission flux (MEF) from contaminated soils of the Idrija Hg-mine region, Slovenia are presented. Representative soil samples with respect to total Hg concentrations (4-417 µg g −1 ) and land cover (forest, meadow and alluvial soil) alongside the River Idrijca were analysed to determine the variation in MEF versus distance from the source, regulating three major environmental parameters… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 47 publications
(68 reference statements)
4
18
0
Order By: Relevance
“…The dynamic flux chamber (DFC) technique was widely used to investigate Hg(0) flux between the air and surface because it is inexpensive, portable, easy to set up and operate (e.g., Kim and Lindberg, 1995;Carpi and Lindberg, 1998;Gustin et al, 2006;Wang et al, 2006;Dommergue et al, 2007;Fu et al, 2008a;Kocman and Horvat, 2010;Edwards and Howard, 2013). Air-surface Hg(0) flux obtained by DFC technique was calculated using Eq.…”
Section: Measurement Of Air-surface Hg(0) Fluxmentioning
confidence: 99%
See 3 more Smart Citations
“…The dynamic flux chamber (DFC) technique was widely used to investigate Hg(0) flux between the air and surface because it is inexpensive, portable, easy to set up and operate (e.g., Kim and Lindberg, 1995;Carpi and Lindberg, 1998;Gustin et al, 2006;Wang et al, 2006;Dommergue et al, 2007;Fu et al, 2008a;Kocman and Horvat, 2010;Edwards and Howard, 2013). Air-surface Hg(0) flux obtained by DFC technique was calculated using Eq.…”
Section: Measurement Of Air-surface Hg(0) Fluxmentioning
confidence: 99%
“…2). Many studies have confirmed that solar radiation is one of the most important drivers for soil Hg(0) emission Choi and Holsen, 2009;Kocman and Horvat, 2010); high surface temperature also facilitates Hg(0) production and subsequent emission (Park et al, 2014). Therefore, the two environmental variables jointly regulate the diurnal pattern of Hg(0) flux.…”
Section: Hg(0) In Ambient Airmentioning
confidence: 99%
See 2 more Smart Citations
“…Soil types, soil moisture and Hg content in soil are also important factors influencing observed Hg 0 flux (Xu et al, 1999;Kocman and Horvat, 2010;Lin et al, 2010a). observed that rainfall and irrigation enhances soil Hg 0 emission by 1 order of magnitude.…”
Section: Air-soil Hg Exchangementioning
confidence: 99%